How Do Histopathological Findings Relate To Cervical Lymph Node Metastasis In Laryngeal Cancer? A Retrospective Study And Literature Review - Belli, Seyda; Yıldırım, Metin; Emre Kaya, Funda; Bilece, Tolga; Faruk Oktay, Mehmet (ENT Updates, 2019)
Purpose: This study aimed to elucidate how histopathological findings relate to the existence of metastases in lymph nodes in a cohort of surgical cases with squamous cell carcinoma of the larynx. Material and Methods: A cohort of cases from the ENT department, who had partial or total laryngectomy and dissection of the neck in the period spanning January 2008 to June 2017 were evaluated retrospectively. 150 cases were deemed appropriate for inclusion in the study. The histopathological notes and clinical findings of these cases were compared to each other. Findings: The glottic group had lower levels of lymphovascular invasion (p<0.05). Tumours staged at T3 or T4 level or endophytic in subtype were, however, more likely to have lymphovascular invasive features (p<0.05). For neoplasms with a high degree of differentiation, it was less frequent to observe invasion of lymphatics, metastasis to the cervical nodes or invasion beyond the capsule (p<0.05). Perineural invasion was not associated with a greater risk of the neoplasm metastasizing to the cervical lymphovasculature, but invasion of the lymphatics did signal an increase in metastasis (p<0.05). Conclusion: Cervical lymphatic metastasis of squamous cell carcinoma of the larynx has a high degree of correlation with histopathological grading.